Фактори, які кондиціонують поліваріантність ефектів бальнеотерапевтичного комплексу курорту Трускавець на інтракардіальну та центральну гемодинаміку - Ружило, С.В. (Інститут фізіології ім. О.О. Богомольця НАН України, 2004)
Показано что, разнообразие эффектов курса бальнеотерапии на курорте Трускавець на гемодинамику может быть сведено методом кластерного анализа к четырем вариантам. Методом дискриминантного анализа выявлены 15 исходных параметров гемодинамики, вегетативной регуляции и обмена электролитов и липидов, закономерно обуславливающих тот или иной вариант бальнеоэффекта. The method of an echocardiography studies reactings intracardial and central hemodynamics of the man on a course balneotherapy on a spa Truskavets'. Outgoing from shifts of main parameters: an index of contractility (IC), frequency of a rhythm (FR), middledynamic pressure (Pm), general peripheral resistance of vessels (GPRV), expulsion time (ET), enddyastolic (EDV), shock (SV) volumes of heart and cardiac output (CО) - is selected 4 types of reacting. Hypotensive bradycardiо-antikinetic reacting registered for 34,8% of persons, is characterized reduce of Pm, rhythm, ET and CО associated with absence of changes SV, EDV, GPRV and IC. For antiresistive tachycardiо-prokinetic type (30,3% of cases) is characteristic combination of increase of a FR, ET and CО with a considerable decrease GPRV. At proresistive antiinotropic tachycardiо-antikinetic type (19,7% of faces) is essentially increased GPRV and FR, reduced IC, ET, EDV, SV and CО. For 15,2% of faces is established antiresistive proinotropic prokinetic type described by a increase of IC, EDV, SV, FR and CО and decrease of GPRV. The type of effects are conditionized by constellation of 15 initial parameters of haemodynamic, vegetative regulation and exchange of lipides and electrolytes and are prognozed by method of disccriminant analysis (correctly 83,3%).